Emerging technologies of employing algae and microorganisms to promote the return-to-field of crop straws: A mini-review - Lu, Qian; Xiao, Yu; Wu, Pengfei (Frontiers in Bioengineering and Biotechnology, 2023)
As an agricultural waste, crop straw enriched with a variety of nutrients is regarded as an important fertilizer resource. In the past, crop straw return-to-field played a key role in the sustainability of agricultural environment, but some problems, such as ammonia loss in ammoniation, low rate of straw decomposition, and high carbon footprint, attracted researchers’ attentions. In this paper, we propose three technical routes, including cyanobacteria-based ammonia assimilation, microorganisms-based crop straw pretreatment, and microalgae-based carbon capture, to address the aforementioned problems. Besides, challenges which may hinder the practical application of these technical routes as well as the potential solutions are discussed in detail. It is expected that this paper could provide new ideas to the practical application of crop straw return-to-field.